Pengaruh Literasi Keuangan dan Penggunaan Teknologi Keuangan terhadap Kepuasan Keuangan Mahasiswa Kabupaten Sleman yang dimediasi oleh Perilaku Keuangan - Viyani, Ari Okta; Putri, Nova Intan Berliana (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2023)
Financial literacy, financial technology, financial behavior, and financial satisfaction are very crucial for young people. This study aims to determine the factors that can produce financial satisfaction for young people. Data were collected by survey technique using online questionnaires. Data were analyzed using SEM-PLS. The results show that financial literacy influences financial behavior. Then, financial satisfaction for young people can be formed through financial literacy and financial technology. This research provides new findings that financial behavior can mediate between financial literacy and financial technology toward achieving financial satisfaction.